Pembangunan Box Culvert untuk Penanggulangan Banjir pada Jalan Utama Kelurahan Talang Rimbo, Kabupaten Rejang Lebong - Dwi Aji Ttriono; Rezi Munizar (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Urban flooding in areas with high transportation activity is an infrastructure problem influenced by increased surface runoff, limited drainage capacity, and changes in land-use characteristics. This study aims to analyze design flood discharge, evaluate existing drainage capacity, and design box culvert dimensions as a flood control solution on the Main Road of Talang Rimbo Village, Rejang Lebong Regency. The research method employs a quantitative approach based on hydrological and hydraulic analysis through calculations of design rainfall using the Gumbel distribution, Mononobe rainfall intensity, and Rational Method flood discharge, as well as an evaluation of channel capacity using Manning’s equation. The results show that the design flood discharge reaches 5.54 m³/s, while the capacity of the existing channel is only 0.28 m³/s, resulting in a capacity deficit of 5.26 m³/s. A box culvert with dimensions of 1.6 m × 1.8 m can increase flow capacity and provide a technical solution to the flooding problem. This study contributes to the development of urban drainage designs based on hydrological and hydraulic approaches to enhance infrastructure resilience against flood risks.